Approaches to understanding and interpreting the risks of red blood cell transfusion in neonates. Issue 4 (21st January 2019) - Keir, A. K.; New, H.; Robitaille, N.; Crighton, G. L.; Wood, E. M.; Stanworth, S. J.
SUMMARY: In this review, we explore how to assess potential harm related to neonatal transfusion practice. We consider different sources of information, including passive or active surveillance systems such as registries, observational studies, randomised trials and systematic reviews. Future research directions are discussed.